FRI0266 Hemodynamic complications in systemic sclerosis patients with various stages of pulmonary arterial hypertension. (23rd January 2014) - Inaba, T.; Hatano, M.; Yao, A.; Maki, H.; Imamura, T.; Shiga, T.; Kinugawa, K.; Nagai, R.; Asano, Y.; Sumida, H.; Takahashi, T.; Toyama, T.; et al.
Abstract : Background: Prognosis of pulmonary arterial hypertension (PH) in systemic sclerosis (SSc) patients is poor. PH is a pathophysiological state defined by an increase in mean pulmonary arterial pressure (mPAP) ≥25 mmHg as assessed by right heart catheterization (RHC) and borderline-PH is defined by mPAP ≥21 mmHg. A rise in mPAP is a late marker of the pulmonary arteries remodeling processes, and the pre-clinical phase of SSc (mPAP <21 mmHg) is largely unknown. Objectives: To examine the hemodynamic characteristics in SSc with various stages from normal pulmonary pressure to PH stages. Methods: Eighty-eight consecutive patients with SSc (80 women and 8 men, 72 limited cutaneous SSc and 16 diffuse cutaneous SSc; mean age 62±11 yr) were assessed by RHC in a single center from May 2005 to December 2011. They were classified into four groups by mPAP (Table): (1) normal pressure (NP) group; mPAP <15mmHg, (2) pre-PH group; 15≤ mPAP <20mmHg, (3) borderline-PH group; 21≤ mPAP <25 mmHg, (4) PH group; mPAP ≥25mmHg. Results: Age was not different among 4 groups. The differences in the plasama levels of brain natriuretic peptide (BNP), peak VO2, and % vital capacity/% diffusing capacity for carbon monoxide (%VC/%DLCO) changed in parallel with PH stage. In only PH group, heart rate (HR) was significantly increased. Even in NP group, pulmonary vascular resistance (PVR) was already increased, which might imply that pulmonary arteries in SSc were impaired in the very early stage. In pre-PH group, while PVR slightly increased, cardiac index (CI) markedly decreased below normal limit. Decreases in stroke volume index (StVI) became significant in not only PH but also borderline-PH and pre-PH groups. Conclusions: According to our results, pulmonary arterial remodeling progresses faster than expected from mPAP in SSc patients, and earlier pharmacological intervention may be beneficial. Disclosure of Interest: None Declared